Estrategias didácticas para el desarrollo de la conducta neuromotriz en los niños del primer año de la Escuela de Educación Básica Fiscal “Alfonsina Storni” de la Parroquia Unamuncho, Cantón Ambato, Provincia de Tungurahua, Período Académico 2014 – 2015 - Fernández Naranjo, Jaqueline Del Rocío (2016)
This study is of great importance to education in particular for the first year of basic education, which is part of the problem that goes as follow: How do teaching strategies influence the development of neuro motor behavior in children in the first year of basic education in the Alfonsina Storni school, in a parish called Unamuncho located in Ambato, province of Tungurahua, term 2014 - 2015? The purpose was to identify the teaching strategies used by teachers for the development of neuro motor behavior and the establishment of development areas neuro motor behavior in children freshmen basic through description of its characteristics. From the previous analysis the need to develop a methodology of teaching strategies to develop neuro motor behavior in children at the "Alfonsina Storni" school is concluded. The contribution of this research work is in the structuring of activities to be implemented in the children's first year of basic education to enhance certain abilities and skills since childhood both in terms of fine motor skills as thick. It was considered teaching strategies that give those sequences in considering mutual learning from different perspectives: teacher, student and content, laterality and motor skills: Three essential and necessary elements to be developed by children were considered. The methodology used was explanatory as it allowed a study of all the events that have given rise to the present concerning the development of neuro motor behavior and results regarding the use of teaching strategies to describe and analyze them in terms of their influence on the which is part of a theoretical basis based on tangible and intangible bibliographic material. More than these inductive and deductive methods with their analytical and synthetic processes applied. An observation technique for children was used for data collection and information gathering teachers a survey was applied. Thus, the present study as a result structure a methodological guide that includes teaching strategies that develop neuro motor behavior in children, containing activities such as jumping, running, know the environment is located with requirements for consolidation which are recommended to be applied..